208k views
4 votes
3x + 5y = 2 show that (-1,1) is the solution to this equation

2 Answers

1 vote

plug in -1 in for x and 1 in for y to make the equation 3(-1) + 5(1) = 2. when you multiply them you get -3 + 5 =2. once you simplify this you get 2=2 which is true.

User Negabaro
by
4.7k points
2 votes
We can show that (-1,1) is a solution by plugging it into the equation for x and y values. Let’s first rewrite the equation:

3x + 5y = 2

Now we can plug in our values:

x = -1
y = 1

so,

3(-1) + 5(1) = 2

-3 + 5 = 2

Because this equation is true, the ordered pair (-1,1) is a solution.
User Miqe
by
5.2k points